Trade Openness and Its Impact on Wage Rates and Employment in the U.S. Retail Sector - Pilosov, Ilya; Šváb, Patrik; Tomášek, Jakub; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines how trade openness and tariff policy have influenced wage dynamics and employment outcomes in the U.S. retail sector between 2010 and 2024, with particular attention to the structural shifts that occurred during the Trump administration. Although retail is a non-tradable downstream sector, its heavy dependence on imported consumer goods makes it highly sensitive to global trade conditions, supply-chain disruptions and policy-driven cost shocks. Building on classical and modern trade theory, including the Stolper-Samuelson framework, New Trade Theory, and Melitz-type firm heterogeneity, the thesis contextualizes how global value chains and competitive pressures transmit into labor-market outcomes. A descriptive analysis shows persistently high import penetration, growing reliance on global sourcing, stagnant real wages, and a gradual reallocation of employment from in-store jobs toward logistics and e-commerce roles. Using quarterly data from 2010-2024, three AR(1) time-series models assess the effects of trade openness and tariffs on nominal retail wages and retail employment share. The results indicate that trade openness exhibits no significant effect under stable policy conditions but becomes economically meaningful during the Trump presidency: interaction terms reveal that greater openness during 2017-2020 slightly reduced nominal wage growth and exerted downward pressure on retail’s employment share. Tariff-based models similarly show that tariff increases had a negative marginal effect on nominal wage levels. Overall, the findings suggest that short-run labor-market adjustments in retail are driven less by openness itself and more by policy-induced cost shocks, uncertainty and supply-chain frictions. Long-run sectoral trends that slow wage growth, rising inequality, and structural job reallocation, remain largely unaffected by temporary reversals in U.S. trade policy.
Vedoucí práce: Patrik Šváb
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses